2019
DOI: 10.3390/v11100951
|View full text |Cite
|
Sign up to set email alerts
|

Look Who’s Talking: T-Even Phage Lysis Inhibition, the Granddaddy of Virus-Virus Intercellular Communication Research

Abstract: That communication can occur between virus-infected cells has been appreciated for nearly as long as has virus molecular biology. The original virus communication process specifically was that seen with T-even bacteriophages—phages T2, T4, and T6—resulting in what was labeled as a lysis inhibition. Another proposed virus communication phenomenon, also seen with T-even phages, can be described as a phage-adsorption-induced synchronized lysis-inhibition collapse. Both are mediated by virions that were released f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 137 publications
(321 reference statements)
6
59
0
Order By: Relevance
“…This explanation resembles results for other forms of phage-phage interaction previously found in Escherichia coli -infecting phages [17,18]. In the obligately lytic T-even phages, both the length of the latent period of an infection and the subsequent burst size increase if additional phages adsorb to the cell while it is infected -a process called lysis inhibition [18][19][20]. In the temperate phage λ, the the propensity towards lysogeny increases with the number of co-infecting virions, called the multiplicity of infection (MOI) [21].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This explanation resembles results for other forms of phage-phage interaction previously found in Escherichia coli -infecting phages [17,18]. In the obligately lytic T-even phages, both the length of the latent period of an infection and the subsequent burst size increase if additional phages adsorb to the cell while it is infected -a process called lysis inhibition [18][19][20]. In the temperate phage λ, the the propensity towards lysogeny increases with the number of co-infecting virions, called the multiplicity of infection (MOI) [21].…”
supporting
confidence: 87%
“…Other modelling work has shown that if phages, lysogenised cells, and susceptible cells coexist for long periods of time, the susceptible cell density becomes low because of phage exploitation, and less and less virulent phages are selected [15,16].Erez et al [9] propose that the arbitrium system may have evolved to allow phages to cope with the changing environment during an epidemic, allowing the phages to exploit available susceptible bacteria through the lytic cycle when few infections have so far taken place and hence the concentration of arbitrium is low, while entering the lysogenic cycle when many infections have taken place and the arbitrium concentration has hence increased. This explanation resembles results for other forms of phage-phage interaction previously found in Escherichia coli -infecting phages [17,18]. In the obligately lytic T-even phages, both the length of the latent period of an infection and the subsequent burst size increase if additional phages adsorb to the cell while it is infected -a process called lysis inhibition [18][19][20].…”
supporting
confidence: 74%
“…Also, it is important to recognize that temperate phages, upon initial virion adsorption, often infect lytically rather than lysogenically [80], meaning that the same virus from the same environment could potentially be isolated using different isolation methods both as a provirus and as a virion. This ability of a phage to infect other than lysogenically commonly is described as their lytic potential, but it seems to be modifiable in response to how many hosts are present that virions can infect [81][82][83][84][85]. Further information on different proposed methods that bacteriophages use to regulate lysis-lysogeny conversion can be found in the literature (see [84,[86][87][88][89][90][91][92]).…”
Section: Techniques For Isolating Virusesmentioning
confidence: 99%
“…S5). In addition, the lysis-inhibition (LIN) defect caused by the original S12 frame-shift mutation in the T4 Spackle gene, which leads to the replacement of nine amino acids at the C-terminus with an unrelated sequence (Abedon, 1999(Abedon, , 2019Emrich, 1968;Kai et al, 1999), may suggest that the last -helix (5) of Spackle is important for lysozyme interaction. Phage T4 has a cytoplasmic soluble (gpe) lysozyme that is responsible for degrading the cell wall of the host to release progeny particles.…”
Section: Discussionmentioning
confidence: 99%